(untitled) (Research, Society and Development, 2022)
In recent years, discussions on environmental issues have reached all economic sectors in the search for actions to reduce the impacts of degradation on the environment and the Circular Economy has been adopted as a viable alternative for the possibility of evaluating and rethinking the current economic model, to ensure that scarce resources are not depleted. The purpose of this article is to identify research related to Circular Economy and Innovation. For this, the bibliographic study was adopted as a methodological procedure, as a qualitative and exploratory approach. The criteria adopted was the open research horizon regarding the initial date, but limited to the year 2020, the database of the Brazilian Digital Library of Theses and Dissertations (BDTD) was considered, considering the combination "Circular Economy" as keywords. and “Innovation” considering all fields, where 12 thesis and dissertation works were considered. The results show that studies related to circular economy and innovation in the BDTD database were strongly developed in the South and Southeast regions, which have been considered as research centers on the subject, especially at USP and UFRGS. The Production Engineering Graduate Programs are the most interested in studying this topic and their main approach is the Case Study due to its greater representativeness.